2015
DOI: 10.1161/hypertensionaha.114.04691
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Targeted Angiotensin-Converting Enzyme 2 Overexpression Attenuates Neurogenic Hypertension by Inhibiting Cyclooxygenase-Mediated Inflammation

Abstract: Overactivity of the renin angiotensin system (RAS), oxidative stress, and cyclooxygenases (COX) in the brain are implicated in the pathogenesis of hypertension. We previously reported that Angiotensin-Converting Enzyme 2 (ACE2) overexpression in the brain attenuates the development of DOCA-salt hypertension, a neurogenic hypertension model with enhanced brain RAS and sympathetic activity. To elucidate the mechanisms involved, we investigated whether oxidative stress, mitogen activated protein kinase signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 45 publications
(83 reference statements)
3
54
0
Order By: Relevance
“…Previous findings have emphasized the role of inflammatory cytokines in the PVN in mediating sympatho-excitation and autonomic function during various cardiovascular diseases, including hypertension. 4, 5, 30 In our study, we found that B1R gene deletion reversed the DOCA-salt hypertension-induced autonomic dysfunction and sympatho-excitation, and improved baroreflex sensitivity, suggesting a central role for B1R activation during neurogenic hypertension.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…Previous findings have emphasized the role of inflammatory cytokines in the PVN in mediating sympatho-excitation and autonomic function during various cardiovascular diseases, including hypertension. 4, 5, 30 In our study, we found that B1R gene deletion reversed the DOCA-salt hypertension-induced autonomic dysfunction and sympatho-excitation, and improved baroreflex sensitivity, suggesting a central role for B1R activation during neurogenic hypertension.…”
Section: Discussionsupporting
confidence: 52%
“…5 To assess the effects of B1R deletion on baroreflex function, we determined spontaneous baroreflex sensitivity (SBRS) using the sequence method. SBRS was significantly reduced in WT+DOCA mice compared to sham (Figure 2F).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations